Reclaiming Agency: Subverting Patriarchy and Reconfiguring Gender in Enola Holmes (2020) - Saputra, Felicia Celine; Rumondor, Imanuela Kimberly (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2025)
In the 21st century, feminism continues to grapple with persistent challenges, including gender pay gaps, underrepresentation in leadership roles, and ongoing debates over reproductive rights that echo historical struggles for equality. Drawing connections to feminist protests during the Victorian era. Using a qualitative method, this study employed feminist theory, particularly the works of Judith Butler (1990), Betty Friedan (1963), and Charlotte Brontë (1847) to analyze the 2020 film Enola Holmes. The film is examined as a cultural text that subverts patriarchal norms and offers a narrative of female empowerment by: 1) presenting characters, such as Enola and her mother, Eudoria, who reject conventional feminine behavior in favor of self-defense, independence, and intellectual curiosity; 2) critiquing institutional constraints through the depiction of rigid gender stereotypes enforced by settings like the finishing school; and 3) illustrating how Enola’s defiance of familial and societal expectations empowers her to reclaim agency and reshape her future. This article contributes to ongoing academic discourse on gender representation in media by demonstrating how modern adaptations of historical settings can illuminate contemporary feminist issues and challenge established societal norms regarding gender equality.